Isu-isu Pendidikan Guru dalam Kajian Pedagogi Kritis di Indonesia - Sholihah, Mar'atus; Sholihah, Nila Ma'rifatus; Aminullah, Aminullah; Masrukhin, Akhmad Rudi; Nahrowi, Moh.; Fadillah, Fadillah (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Teacher education issues are the fundamental concerns underlying critical pedagogy studies in Indonesia. Numerous issues have emerged, becoming topics of public discourse. These issues have arisen because teachers’ competencies are not being realized even after they have undergone teacher education. Among the issues are a teacher’s motivation to teach, the ability of teachers to enhance the quality of education through the improvisation of the hidden curriculum, and the demand for critical thinking among students. This study was conducted using qualitative methods with a literature review approach, gathering data on teacher education issues through a theoretical analysis of diverse literature related to the observed phenomena. The results indicate that most of the emerging educational issues are indeed rooted in the degradation of teacher education, which ultimately leads to a decline in the quality of education. Addressing this requires improving teacher education—from enhancing teachers’ motivation to teaching to developing the competencies that can be internalized through the teaching profession.